An integrated geology and reservoir engineering approach for modelling of a giant fractured basement reservoir. (2015) - Dang, Cuong T.Q.; Chen, Zhangxing; Nguyen, Ngoc T.B.; Phung, Thuoc H.
A great portion of the world's oil reserves is contained in naturally fractured reservoirs (NFRs). As the conventional oil and gas reservoirs have become significantly depleted whereas energy demand sharply increases, the NFRs play an important role in oil exploration and make a large contribution toward oil and gas production worldwide. This paper aims to introduce a historical case study of a successful development plan for a giant fractured granite basement reservoir with a unique geological characterisation. A better geological understanding about the complexity of such a naturally fractured basement reservoir is provided within a simulation strategy in order to optimise successfully its oil exploitation. With our rich experiences in exploration and production of hydrocarbons in fractured basement granite rock for more than 20 years, it is a valuable case study for both current and future development planning of basement reservoirs elsewhere in the world. [Received February 5, 2013; Accepted November 25, 2013].